"Green" Synthesis of Metal‐Organic Frameworks. Issue 27 (9th June 2016) - Reinsch, Helge
Abstract : Research in the field of metal‐organic frameworks (MOFs) has been for a long time devoted to the synthesis of new compounds and the understanding of their outstanding properties. Just in the recent four or five years there has been an emerging interest in up‐scaling of synthesis procedures and the adjustment of synthesis conditions towards industrial requirements. This probably originates from the fact that, while some MOFs are already commercially available, there is still no field of application in real life which MOFs are able to fit in. One reason for this might be the attributed to the common synthetic procedures which are often unsuitable for preparations at pilot or industrial scale. Thus a recent focus in MOF research is the finding of synthesis conditions which employ non‐hazardous reactants at relatively mild synthetic conditions, producing also less waste than conventional procedures. In brief: The "green" synthesis of MOFs. This microreview is intended to give some examples of the efforts made in this field of research and show some perspectives for the future. Abstract : During the recent years the research in the field of MOFs has gradually shifted towards a focus on more sustainable and industrially feasible conditions. This microreview gives several concise examples from this emerging field of research and also depicts some perspectives.